xPROT : OBJECT-ORIENTED PROTOTYPING MODEL - A. Nuri BAŞOĞLU (Pamukkale University Journal of Engineering Sciences, 2000)
Even relational database management systems have now become the standard for data processing applications; object oriented database systems are being developed to meet the complex data modeling requirements. In this paper an object-based system, xPROT, is introduced which could be used for rapid program development. System includes some pre-defined methods and classes as Menu, Report, View, Table. In xPROT the schema as well as the data manipulation is expressed by the same command-based language. Expressiveness, easiness and flexibility in terms of data modeling power is investigated.